A 15‐year retrospective study on the prevalence of onychomycosis in psoriatic vs non‐psoriatic patients: A new European shift from dermatophytes towards yeast. Issue 8 (23rd May 2019) - Gallo, Lucia; Cinelli, Eleonora; Fabbrocini, Gabriella; Vastarella, Maria
Summary: Because of their similar clinical presentation, discrimination between nail psoriasis and onychomycosis often is difficult. We aim to investigate the actual frequency of onychomycosis in psoriatic patients and to compare it between psoriatic and non‐psoriatic patients. This retrospective study included a total of 9281 patients, referring to our Mycology Laboratory from September 2003 to May 2018. The patients are divided into two groups: PsoGroup (patients with psoriasis) and non‐PsoGroup (non‐psoriatic patient). Direct microscopic examination with 20% KOH and culture was carried out in both groups. In PsoGroup (711 patients, 59.50% female, 40.50% male, median age of 52.22 ± 15.01), the prevalence of onychomycosis was 49.08%. On the other hand, in non‐PsoGroup (8570 patients (71.65% female, 28.35% male, median age of 48.51 ± 19.31 years), the prevalence of onychomycosis was 51.30%. There was no statistically significant difference between the prevalence of onychomycosis in PsoGroup 49.08% (349/711) compared to 51.30% (4397/8570) of non‐PsoGroup ( P = 0.2578). However, yeasts were significantly more prevalent in non‐psoriatic than in psoriatic patients ( P = 0.0144.). In our Mycological Laboratory, we observed a similar prevalence of onychomycosis in psoriatic patients and non‐psoriatic patients. However, the spectrum of fungal species isolated was different from each other, with a higher prevalence of yeasts in non‐PsoGroup that reflect a recent oriental trends.